Bone remodeling and regulating biomarkers in women at the time of breast cancer diagnosis - Yao, Song (Breast Cancer Res Treat, 2016)
The majority of breast cancer patients receive endocrine therapy, including aromatase inhibitors known to cause increased bone resorption. Bone-related biomarkers at the time of breast cancer diagnosis may predict future risk of osteoporosis and fracture after endocrine therapy. In a large population of 2,401 female breast cancer patients who later underwent endocrine therapy, we measured two bone remodeling biomarkers, TRAP5b and BAP, and two bone regulating biomarkers, RANKL and OPG, in serum samples collected at the time of breast cancer diagnosis. We analyzed these biomarkers and their ratios with patients’ demographic, lifestyle, clinical tumor characteristics, as well as bone health history. The presence of bone metastases, prior bisphosphonate (BP) treatment and blood collection after chemotherapy had a significant impact on biomarker levels. After excluding these cases and controlling for blood collection time, age, race/ethnicity, body mass index, physical activity, alcohol consumption, smoking, and hormonal replacement therapy were significantly associated with bone biomarkers, while vitamin D or calcium supplements and tumor characteristics did not. When prior BP users were included in, recent history of osteoporosis and fracture was also associated. These findings support further investigation of these biomarkers with bone health outcomes after endocrine therapy initiation in women with breast cancer.